Environmental Sanitation And Dengue Hemorrhagic Fever - Marlinang I Silalahi; Tonggo Apriliani (TOUR HEALTH JOURNAL, 2022)
Background: Dengue  hemorrhagic  fever  (DHF)  is  a  disease caused  by  the  dengue  virus which  belongs  to  the  arthropod borne virus. DHF is transmitted through mosquitobites from the genus Aedes. This disease is related to environmental conditions and community behavior. Purpose: The purpose of  this study is to determine the relationship of enviroment sanitation to the incident of DHF  in Martubung Village,Medan Labuhan subdisctrict. Method: This  type  of  study  is  an  analytical  survey  with  across sectional method.  The  variables  used  in this  study  are  waterreservoirs,   landfills, and wastewater drain. There are 122 respondents in  this research. Data  collection  using  observation sheets and data analysis methods using Chi-square   with   a significance level of 0.05. Result: The  results  of data analysis showed that there was a relationship between water reservoirs (p=0,025),    landfills (p=0,023) and wastewater  (p=0,01) with  the  incidence of DHF in the Martubung Village, Medan Labuhan subdisctrict. Conclusion: It is better for each respondent to be more concerned to always maintain a healthy condition of home environment sanitation, it is necessary to carry out routine cleaning  as  well as mutual cooperation activities to clean the environment.